Effect of Proteolytic Agents on Microleakage of Etch and Rinse Adhesive Systems - Shahin Kasraei; Ebrahim Yarmohammadi; Maryam Farhadian; Mona Malek (Universidade Estadual de Campinas, 2017)
Objective: this study aimed to assess the effect of treatment of phosphoric acid etched dentin surface with 5% bromelain enzyme and Nd:YAG laser prior to the use of etch and rinse adhesive systems on microleakage margins of class V composite restorations. Materials and Methods: sixty sound premolar teeth were selected. Standard class V cavities were prepared in the buccal and lingual surfaces of each teeth. Preparation in that way 1 mm of the cavity was above and 1 mm of it was below the cementoenamel junction. The teeth were then randomly divided into three groups including 20 teeth(40cavities  in each gorup). Two ethanol base etch and rinse system (Adper Single Bond and OptiBond Solo) was applied in each group. In the control group, cavities were etched with 37% phosphoric acid. Adper Single Bond was applied to 20 and OptiBond Solo was applied to the remaining 20 cavities and they were restored with Z250 composite (n=40). The same procedures were performed in bromelain and Nd:YAG laser groups with the difference that prior to the application of adhesive, aqueous 5% bromelain was applied in bromelain group while Nd:YAG laser was irradiated in laser group. All teeth were thermocycled and their apices were sealed with sticky wax. The tooth surfaces were coated with nail varnish except for 1 mm around the restoration margins, and the teeth were then immersed in fuchsine and sectioned by a diamond disc into mesial and distal halves. Marginal microleakage at both sides was determined and scored under a stereomicroscope at x40 magnification. Then data were analyzed using the Kruskal Wallis and Mann Whitney tests (α=0.05). Results: according the result of Mann Whitney test, Cervical margins showed significantly higher microleakage than the occlusal margins (P=0.000) but no significant difference was noted in microleakage of occlusal (P=0.362) or gingival (P=0.147) margins among the three groups by Kruskal Wallis test. Conclusion: in conclusion, application of proteolytic agents(5% bromelain solution and Nd:YAG laser)  on acid-etched dentin surface prior to the application of adhesive has no significant effect on marginal microleakage of class V composite restorations.